2019
DOI: 10.5603/pjnns.a2019.0036
|View full text |Cite
|
Sign up to set email alerts
|

A new therapeutic strategy with istradefylline for postural deformities in Parkinson’s disease

Abstract: Aim of the study. Postural deformities are common in Parkinson's disease (PD) patients. Several treatment options have been reported, but responses to these treatments appear unpredictable. Istradefylline is a novel drug for PD. Cases of PD patients whose postural deformities were improved after withdrawal of dopamine agonists and initiation of istradefylline are presented. Materials and methods. Four consecutive patients with postural deformities including antecollis, Pisa syndrome, and camptocormia were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The authors also noted that three of the patients showed remarkable improvements in the timed up and go (TUG) test, although results were not consistent across the full group of patients [141]. In another case series, four consecutive patients with postural deformities (antecollis, Pisa syndrome, and camptocormia) converted from a dopamine agonist to istradefylline showed postural improvements without deterioration of motor symptoms (istradefylline was initiated after an average of 1.3 months following dopamine agonist withdrawal) [145]. Axial symptoms are hard to mimic in animal models, and it is difficult to speculate on the mechanism of A 2A antagonist effects.…”
Section: Preclinical and Clinical Data Evaluating Istradefylline For mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also noted that three of the patients showed remarkable improvements in the timed up and go (TUG) test, although results were not consistent across the full group of patients [141]. In another case series, four consecutive patients with postural deformities (antecollis, Pisa syndrome, and camptocormia) converted from a dopamine agonist to istradefylline showed postural improvements without deterioration of motor symptoms (istradefylline was initiated after an average of 1.3 months following dopamine agonist withdrawal) [145]. Axial symptoms are hard to mimic in animal models, and it is difficult to speculate on the mechanism of A 2A antagonist effects.…”
Section: Preclinical and Clinical Data Evaluating Istradefylline For mentioning
confidence: 99%
“…The relationships between psychiatric functions, sleep-wake control, and adenosine A 2A receptors (located in the basal ganglia and limbic regions) have already been extensively studied in animal models [135] and several small open-label studies have explored the potential utility of istradefylline in the management of non-motor symptoms, such as mood disorders, sleep disturbance, fatigue, and urinary disturbance, as well as difficult-to-treat axial symptoms, such as freezing of gait and posture abnormality (Table 4) [136][137][138][139][140][141][142][143][144][145][146].…”
Section: Preclinical and Clinical Data Evaluating Istradefylline For mentioning
confidence: 99%
“…Second, on the hypothesis stated above, the clinical effect and reliability of A 2A antagonists as symptomatic treatment observed in PD clinical studies can be explained by the A 2A receptor-mediated amelioration of the thalamocortical system. Indeed, recent open-label clinical/ case studies have provided an indication that A 2A antagonists may also improve/ameliorate gait disorder or postural abnormality in PD [86][87][88][89][90][91]. This mechanism can be discussed in terms of the A 2A antagonism-induced suppression of GPi/SNr outputs to the brainstem system, including the pedunculopontine tegmental nucleus (PPN) which regulates gait and posture -as GABAergic suppression of PPN activity from the basal ganglia is thought to be responsible for these components of PD [92,93].…”
Section: Future Aspects Of Adenosine a 2a Receptor-mediated Motor Regmentioning
confidence: 99%
“…One recently published research reported that postural deformities caused by dopamine agonists generally improve less than two weeks after dopamine agonist withdrawal. I stradefylline which is used as an add-on treatment to levodopa/carbidopa in adults with PD experiencing "off " episodes can be a potential therapeutic option in postural deformities like PS [83].…”
Section: Diff Erential Diagnosismentioning
confidence: 99%